2003
DOI: 10.1249/01.mss.0000048725.15026.b5
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Training Lowers Resting Blood Pressure and Modulates Autonomic Control

Abstract: It is concluded that isometric training at a moderate intensity elicits a hypotensive response and a simultaneous increase in vagal modulation in older adults with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
231
6
25

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(287 citation statements)
references
References 20 publications
14
231
6
25
Order By: Relevance
“…Taylor et al 17 , on the other hand, have observed an increase on the vagal modulation, demonstrated by the spectral analysis of the tachogram, in elders with arterial hypertension that were submitted to an isometric handgrip training for 10 weeks. Selig et al 18 have verified that three months of resisted exercise of moderate intensity, produced modifications on the autonomic modulation of patients with cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al 17 , on the other hand, have observed an increase on the vagal modulation, demonstrated by the spectral analysis of the tachogram, in elders with arterial hypertension that were submitted to an isometric handgrip training for 10 weeks. Selig et al 18 have verified that three months of resisted exercise of moderate intensity, produced modifications on the autonomic modulation of patients with cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not true for individuals whose autonomic modulation over the cardio-vascular system is modified not only because of the physiological aging process, but also by the presence of diseases such as arterial hypertension 17 and cardiac failure 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Foram encontradas 12 referências sobre o treinamento com pesos em longo prazo e a PA de repouso em normotensos (7,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) e seis referências em hipertensos (5,32,(40)(41)(42)(43) . Dos estudos com normotensos, duas referências possuíam dois grupos experimentais (35,37) .…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified
“…Em relação aos estudos com hipertensos, quatro reportaram aumento significativo na força (5,32,40,41) ; três, redução na PAS (5,41,43) ; dois, redução na PAD (5,40) . Somente um estudo mostrou redução na PAS e PAD e aumento na força (5) .…”
Section: Treinamento Com Pesos E Pressão Arterial De Repousounclassified
See 1 more Smart Citation